Stress fatigue crack propagation analysis of crane structure based on acoustic emission. (January 2020) - Xu, Bin; Wu, Qi
Highlights: A two-parameter fatigue crack growth model was adopted in theoretical analysis. Response surface was advanced to predict the fatigue life of steel plate. Acoustic emission technique was proposed to detect the crack propagation. The proposed method was applied in fatigue crack propagation of gantry crane. Abstract: Gantry crane is a widely used equipment in logistics fields. Stress fatigue crack propagation is an important fatigue mode of gantry crane in services. Based on theoretical analysis and acoustic emission (AE) test, A new crack propagation analysis method was proposed in this investigation. A two-parameter basis function was adopted to analyze crack propagation of steel Q235B, and the response surface was modeled to predict the fatigue life of steel specimen, moreover AE technique was advanced to detect the crack propagation, where layout of AE sensors was optimized to achieve a precise result. Consequently the proposed method was applied in practical box-girder crack propagation analysis. By comparison with theoretical analysis, it indicated that this method was precise and could be applied in practical engineering.